A rising necessity: Liver retransplantation: A single center experience (Annals of Medical Research, 2021)
Aim: Compared to primary liver transplantation, poor outcomes still remain an issue for liver retransplantation. Materials and Methods: We used registry data from our liver transplantation unit to perform a retrospective cohort study on liver retransplantations performed between January 2012 and October 2019. We considered patients who underwent retransplantation at least one month after primary transplantation as the late group. Patients who had retransplantation within the first month after the first transplantation were considered the early group. We analyzed features of patients, indications, donor types, characteristics of operations, and outcomes. Results: Among 782 patients who underwent liver transplantation, 29 patients underwent retransplantation in our center. Of these 29 patients, 19 patients were in the early group, while 10 patients were in the late group. The 3-year patient survival rates were 47.3% and 80% for the early and late groups, respectively. The overall 1-year survival rate for all retransplanted patients was 58.6%. Conclusion: Despite better results reported for liver retransplantation, there are poor outcomes compared with primary transplantation, especially in the early group. However, the necessity of retransplantation increases every passing year in spite of a shortage of donors. Thus, the justification for liver retransplantation remains controversial.
Keywords: Deceased donor; liver graft failure; living donor